1997
DOI: 10.1016/s0925-4439(97)00064-1
|View full text |Cite
|
Sign up to set email alerts
|

Mutation in an α1-antitrypsin enhancer results in an interleukin-6 deficient acute-phase response due to loss of cooperativity between transcription factors

Abstract: We previously reported that a mutation in a 3' enhancer region of the alpha1-antitrypsin (AAT) gene is associated with chronic obstructive airways disease (COAD). During the acute-phase response the plasma concentration of AAT increases approximately 3-fold and this effect is mediated primarily by interleukin-6 (IL-6). We demonstrate, by transfection of Hep G2 cells, that the AAT gene contains at least two enhancers, one at the 5' end of the gene which is dominant under basal conditions, and another at the 3' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 17 publications
4
34
0
Order By: Relevance
“…For example, in lung-derived epithelial cells (HTB 58), in lung adenocarcinoma cells (HTB 55) and in human alveolar epithelial cells neither IL-1b nor IL-6 had any influence on a1-PI secretion [3,31,32]. In contrast, a1-PI release was found to be enhanced by those cytokines in hepatocytes, cornea cells, articular chondrocytes and monocytes/macrophages [4,5,33,34]. Taken together, these data could imply that the absence of the effect of IL-1b and IL-6 on a1-PI release might be specific for alveolar and intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…For example, in lung-derived epithelial cells (HTB 58), in lung adenocarcinoma cells (HTB 55) and in human alveolar epithelial cells neither IL-1b nor IL-6 had any influence on a1-PI secretion [3,31,32]. In contrast, a1-PI release was found to be enhanced by those cytokines in hepatocytes, cornea cells, articular chondrocytes and monocytes/macrophages [4,5,33,34]. Taken together, these data could imply that the absence of the effect of IL-1b and IL-6 on a1-PI release might be specific for alveolar and intestinal epithelial cells.…”
Section: Discussionmentioning
confidence: 98%
“…Transfection studies indicate that presence of this polymorphism results in a reduced ability to upregulate AAT production in response to IL-6 stimulation. 8 Preliminary in vivo and in vitro studies also suggest that the effect of the native 1237A variant is to decrease the AAT response to infections and stimulation by other cytokines 15 and (unpublished observations).…”
Section: Discussionmentioning
confidence: 87%
“…7 A G?A polymorphism present 1237 bases downstream from the end of the last exon has previously been shown by transfection studies to result in diminished reporter gene expression in response to the acute phase cytokine, interleukin-6. 8 These data, together with studies investigating the interactions between transcription factors in the enhancer where the mutation is located suggest that the mutation may compromise the normal AAT acute-phase response, and these individuals would have an impaired response to infection. 8 Against this background, the primary aim of the current study was to examine the hypothesis that the AAT 3' enhancer polymorphism is associated with greater pulmonary disease severity in CF.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In one study, a polymorphism in the 3' flanking region of the API gene has been reported to be present in 17% of patients with COPD but in only 5% of the general population of the United Kingdom (158). Although it is not associated with abnormal API serum level or function, it has been suggested that this polymorphism lies within an enhancer sequence and may impair the acute phase increase in API expression (158,159).…”
Section: Definition and Pathophysiology Of Copdmentioning
confidence: 99%